Comparison of augmented Berlin-Frankfurt-Münster (BFM) and BFM 2000 treatment protocols in children diagnosed with high-risk acute lymphoblastic leukemia - Özer, Samet; Ağaoğlu, Fatma Leyla; Karakaş, Zeynep; Ünüvar, Ayşegül; Devecioğlu, Ömer (The European Research Journal, 2024)
Objectives: The main purpose of this study is comparing the augmented Berlin-Frankfurt-Münster (BFM) and BFM 2000 treatment protocols applied to pediatric patients diagnosed with high-risk acute lymphoblastic leukemia (ALL) in our clinic in different years in terms of relapse incidence and survival rates. Methods: When evaluated all patients considering the Children’s Oncology Group (COG) criteria, 53 of our patients who were in the medium or high risk group according to the BFM 2000 protocol and were in the high risk group received treatment with Augmented BFM protocol and 17 of them received the BFM 2000 protocol. Age, gender, bone pathology, physical examination, hepatomegaly, splenomegaly, lymphadenopathy, presence of bleeding, hemogram values, immunophenotype, 8th, 14th and 33rd day treatment response, presence of translocation, central nervous system (CNS), extramedullary involvement, risk group, presence of relapse, time to relapse, follow-up period and hospital stay until maintenance treatment were examined. Results: Event-Free Survival (EFS) and Overall Survival (OS) values of patients were 83.6% and 90.1%, respectively. While EFS was 89.4% and OS was 90.6% in the group receiving the Augmented BFM treatment protocol, EFS was calculated as 71.7% and OS was 88.2% in those receiving the BFM-2000 treatment protocol. Accordingly, when the EFS values of those who received the Augmented BFM treatment protocol were compared with those who received BFM-2000, statistically significant values were found (P<0.01). Conclusions: It was observed that the augmented BFM treatment protocol was more protective against relapses and shortened the duration of hospitalization compared to the BFM 2000 treatment protocol.